p38/JNK Is Required for the Proliferation and Phenotype Changes of Vascular Smooth Muscle Cells Induced by L3MBTL4 in Essential Hypertension - Chaowei Hu; Kun Zuo; Kuibao Li; Yuanfeng Gao; Mulei Chen; Roumu Hu; Ye Liu; Hongjie Chi; Hongjiang Wang; Yanwen Qin; Xiaoyan Liu; Jiuchang Zhong; et al. (International Journal of Hypertension)
Aim. Hypertension is a complicated disorder with multifactorial etiology and high heritability. Our previous work has identified L3MBTL4 as a novel susceptibility gene for the development of essential hypertension, accompanied with activation of p38/JNK. Yet, little evidence has been reported whether p38/JNK contributed directly to L3MBTL4-induced vascular remodeling and exploring the potential mechanism of L3MBTL4 in vascular smooth muscle cells (VSMCs). Methods. We evaluated the contribution of L3MBTL4 on proliferation, migration, and phenotype changes of VSMCs and further explored the critical role of p38 and JNK signaling pathway underlying. Results. In L3MBTL4 transgenic rats, we found that the elevated blood pressure, increased left ventricular hypertrophy, and thickened vascular media layer were significantly relieved by both p38 and JNK inhibitors. Meanwhile, increased cell proliferation, advanced cell cycle progression, greater migratory capability, and synthetic phenotype were observed in L3MBTL4 overexpressed VSMCs, which could be blocked by either p38 or JNK inhibitor. Conclusions. Our findings pinpointed that p38 and JNK were required for the proliferation and phenotype changes of VSMCs induced by L3MBTL4 in hypertension. These novel findings yield new insights into the genetic and biological basis of hypertension and are fundamental for further studies to explore the intervention strategies targeting L3MBTL4 and p38/JNK to counteract the progression of hypertension.